Cell Cycle Dependent Nucleosome Occupancy At Cohesin Binding Sites In Yeast Chromosomes - Liu, Jie (2008)
In the budding yeast, cohesin is loaded onto the chromosome during the late G1 phase, establishes sister chromatid cohesion concomitant with DNA replication, and dissociates by the telophase. Here, using oligonucleotide tiling arrays, we show that, at the anaphase, nearly all of the cohesin binding sites contain nucleosome-free regions. The majority of these sites remain nucleosome-free throughout the cell cycle, consistent with the suggestion of a DNA binding anchoring protein present at these sites, although such a region could also serve as part of a marker for the binding of cohesin in the next cell cycle. However, a third of these sites are remodeled in the G1 phase, being reoccupied by nucleosomes by the G1/S boundary, though their subsequent removal in the S phase appears to be independent of DNA replication. Whether this difference is a result of other functions of cohesin or of the chromatin remains to be elucidated.